Health Information Systems – from Present to Future? - Haux, Reinhold (Methods of Information in Medicine, 2018)
This article is part of the Focus Theme of Methods of Information in Medicine on the German Medical Informatics Initiative. Funded by the German Federal Ministry of Education and Research with about 150 million Euro in its currently starting development and networking phase this initiative has already a significant impact on the development of health information systems in Germany. In this Focus Theme two editorials introduce this initiative, one from the viewpoint of its funding institution and one from the initiative’s accompanying institutions. Then the initiative’s four consortia DIFUTURE (Data Integration for Future Medicine), HiGHmed (Heidelberg-Göttingen-Hannover Medical Informatics), MIRACUM (Medical Informatics in Research and Care in University Medicine), and SMITH (Smart Medical Information Technology for Healthcare) present their concepts and plans. For better readability their manuscripts all contain three major sections on governance and policies, on architectural framework and methodology, and on use cases. As the German Medical Informatics Initiative is a large national experiment, we are convinced that communicating on this initiative already at this early stage to an international audience is of importance.
Keywords: Health information systems; medical informatics; biomedical and health informatics; patient care; research